Patient Explanation of Adherence and Non-Adherence to Venous Leg Ulcer Treatment: A Qualitative Study - Weller, Carolina D.; Richards, Catelyn; Turnour, Louise; Team, Victoria (Frontiers in Pharmacology, 2021)
The aim of this study was to understand which barriers and enablers influence patients’ adherence to evidence-based venous leg ulcer management recommendations in primary care. We adopted a qualitative study design, conducting phone interviews with 31 people with venous leg ulcers in Melbourne, Australia. We applied the Theoretical Domains Framework to the interview guide and coding framework to identify patient behaviour domains. We conducted 31 semi-structured phone interviews between October and December 2019 with patients with clinically diagnosed venous leg ulcers. Participants recruited to the Aspirin in Venous Leg Ulcer Randomised Control Trial and Cohort study were invited to participate in a qualitative study, which was nested under this trial. The following factors influenced patients’ adherence to venous leg ulcer treatment: understanding the management plan and rationale behind treatment (Knowledge Domain); compression-related body image issues (Social Influences); understanding consequences of not wearing compression (Beliefs about Consequences); feeling overwhelmed because it’s not getting better (Emotions); hot weather and discomfort when wearing compression (Environmental Context and Resources); cost of compression (Environmental Context and Resources); ability to wear compression (Beliefs about Capabilities); patience and persistence (Behavioural Regulation); and remembering self-care instructions (Memory, Attention and Decision Making). The Theoretical Domains Framework was useful for identifying factors that influence adherence with multiple evidence-based recommendations for venous leg ulcers management. These factors may inform development of novel interventions to optimise shared decision making and self-care to improve healing outcomes. The findings from this article will be relevant to clinicians involved in management of patients with venous leg ulcers, as their support is crucial to patients’ treatment adherence. Consultation with patients about VLU treatment adherence is an opportunity for clinical practice to be targeted and collaborative. This process may inform guideline development.